Immediate and short-term effects of Mulligan's mobilization with movement on knee pain and disability associated with knee osteoarthritis: A prospective case series - Takasaki, Hiroshi; Hall, Toby; Jull, Gwendolen (Taylor and Francis, 2013)
Manual therapy has proven to be a benefit in the management of knee osteoarthritis (OA), but the effects of the method of Mulligan's mobilization with movement (MWM) have yet to be explored in knee OA. As a first step, this case series investigated MWM's immediate and short-term benefits over three occasions of treatment in 19 patients with knee OA. Patients (71.1 ± SD 13.9 years, 14 females and 5 males) received individually prescribed MWM and performed self-MWM. Outcome measures included: 1) pain intensity (visual analog scales) during walking, ascending and descending stairs, and sit-to-stand; 2) passive flexion and extension range of motion (ROM); and 3) Activities of Daily Living Scale of the Knee Outcome Survey (KOS-ADLS). Pain and ROM were assessed at baseline, after the initial treatment, before the second treatment and at exit following the fourth consultation. The KOS-ADLS was assessed at baseline and at exit. Significant improvements from baseline were detected in flexion ROM and pain scores in all tasks following the initial treatment (P < 0.05/3). The KOSADLS score improved significantly from baseline (67.1% ± SD 16.6%) to exit (86.3% ± SD 12.6%) (P < 0.001). MWM was associated with immediate pain relief and improved knee function, suggesting its potential as a component of early management of knee OA.